Multivariate drought stress response of Norway spruce, silver fir and Douglas fir along elevational gradients in Southwestern Germany - Stangler, Dominik Florian; Miller, Tobias Walter; Honer, Harald; Larysch, Elena; Puhlmann, Heike; Seifert, Thomas; Kahle, Hans-Peter (Frontiers in Ecology and Evolution, 2022)
The conifer tree species Norway spruce (Picea abies), silver fir (Abies alba) and Douglas fir (Pseudotsuga menziesii) are important elements in tree species composition and forest management of Central European forests, but their potential to thrive under anticipated climatic changes is still debated controversially. This study contributes a multivariate analysis of resilience components based on increment cores sampled at breast height of Norway spruce, silver fir and Douglas fir trees growing along elevational gradients in Southwestern Germany. We aimed to gain novel insights into the species-specific and elevational response of tree growth and wood density variables during the extreme drought events of the years 2003 and 2018. Our results for Norway spruce corroborate projections of its ongoing decline during climate change as the reductions of wood density and biomass production indicated high drought sensitivity at all elevations. Moreover, resilience indices of mean tree-ring density, maximum latewood density, tree-ring width and biomass production were even lower after the drought of 2018 compared to the previous drought of 2003. Silver fir, a potential substitute tree species for Norway spruce, showed unexpected results with resistance and resilience indices being significantly lower in 2018 compared to 2003 indicating that silver fir might be more vulnerable to drought than previously expected, especially at low elevations. In contrast, the superior growth rates and higher levels of drought tolerance of Douglas fir were especially pronounced during the drought of 2018, even though high coning intensity was present for all investigated tree species as a possible confounding factor to exacerbate the drought stress effects in the study region.